2006
DOI: 10.1063/1.2183370
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric tunability of SrTiO3 thin films in the terahertz range

Abstract: We have developed an interdigited electrode structure for applying a static electric field to a ferroelectric thin film, which enables nearly full transmission of a perpendicularly polarized terahertz wave. This approach has been used to determine the electric field dependence of the complex permittivity of a SrTiO3 thin film on a sapphire substrate up to about 2THz employing time-domain terahertz spectroscopy. We have demonstrated up to 10% variation of the film permittivity at 300GHz at room temperature indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 13 publications
(18 reference statements)
2
46
0
1
Order By: Relevance
“…It shows a stable averaged value of 18.52 between 0.2 to 1 THz, which is comparable with reported values [2,16,18]. The permittivity of STO is determined by ionic polarization and its dielectric response is governed by the soft mode phonon at 2.8 THz, which causes the high permittivity of STO in the sub-THz range [5,17].…”
supporting
confidence: 86%
See 2 more Smart Citations
“…It shows a stable averaged value of 18.52 between 0.2 to 1 THz, which is comparable with reported values [2,16,18]. The permittivity of STO is determined by ionic polarization and its dielectric response is governed by the soft mode phonon at 2.8 THz, which causes the high permittivity of STO in the sub-THz range [5,17].…”
supporting
confidence: 86%
“…Displacive ferroelectrics such as SrTiO 3 (STO) are characterized by the existence of a polar soft lattice vibration mode responsible for the ferroelectric phase transition [5]. The permittivity of STO single crystal in the sub-THz range is reported to be very high [2,5,16,18] and increases with decreasing temperature, while their permittivity at ∼1.5 to 3 THz is negative [5]. Such properties of STO can lead to interesting applications in THz PC and tunable devices [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 Such layers show an enhanced tunability of the complex microwave and terahertz dielectric function at room temperature as compared to single crystals and unstrained films. [14][15][16] It has been demonstrated that STO/DSO multilayers can be grown on DSO substrates with the aim to increase the total thickness of the strained STO. 7,16 A strong strain and, as a consequence, high values of the subterahertz dielectric function at room temperature can then be maintained across at least 200 nm of the total thickness of STO layers.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the fact that the dielectric constant of ceramics can be regulated by other external stimuli, such as the electric field [39] and the stress field [40], etc., we expect that the temporal response of the proposed active cloak can be much better, though it is beyond the scope of this study.…”
Section: Appendix B: Mechanism Of the Temperature-tunable Cloakmentioning
confidence: 99%